Just culture practice in the aviation industry: recommendations for VietNam airlines - Nguyễn, Hải Anh (2020)
The thesis satisfies the urgency, deals with topical issues and has theoretical and practical significance. The thesis has discussed the basic theoretical issues of Just Culture in the aviation industry. The thesis also analyzed the status of Just Culture in the aviation industry and at Vietnam Airlines. Since then, the thesis has proposed four groups of solutions and recommendations to improve the Just Culture of Vietnam's aviation industry and particularly, in Vietnam Airlines.